2017
DOI: 10.1002/brb3.709
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing safety in Parkinson's disease after zona incerta deep brain stimulation

Abstract: ObjectivesThe objective of this study was to examine swallowing function in patients with Parkinson's disease before and after caudal zona incerta deep brain (cZI DBS) surgery. The aims were to examine the effect of cZI DBS on swallowing safety regarding liquid and solid food, as well as to identify the effect of cZI DBS on body mass index (BMI) and specific items from part II of the Unified Parkinson's Disease Rating Scale (UPDRS).Materials and MethodsThe median age of the 14 patients was 57 years (range 46–7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Sundstedt et al found no significant difference in SWAL-QOL score and VA scale score 12 months after the DBS at ON medication state in nine PD patients with bilateral cZi ( 23 ). Sundstedt et al also did a prospective longitudinal study on 14 PD patients with bilateral cZi, extending their previous report on swallowing function, before and after DBS at ON medications and ON DBS vs. OFF DBS state by FEES ( 24 ). They found that cZi DBS did not have a negative impact on swallowing function, with no changes on PA scores, pharyngeal residual or premature spillage, although the medication was cut down by one-third post-operatively.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…Sundstedt et al found no significant difference in SWAL-QOL score and VA scale score 12 months after the DBS at ON medication state in nine PD patients with bilateral cZi ( 23 ). Sundstedt et al also did a prospective longitudinal study on 14 PD patients with bilateral cZi, extending their previous report on swallowing function, before and after DBS at ON medications and ON DBS vs. OFF DBS state by FEES ( 24 ). They found that cZi DBS did not have a negative impact on swallowing function, with no changes on PA scores, pharyngeal residual or premature spillage, although the medication was cut down by one-third post-operatively.…”
Section: Resultsmentioning
confidence: 58%
“…LFS of STN was found to have beneficial effect on dysphagia compared to HFS in patients with FOG refractory to usual HFS of STN (16,17). DBS targeting the post-subthalamic area and caudal zona incerta (PSA/cZi) was thought to be associated with fewer side effects compared to ventralis intermedius (ViM) or STN (21), including the swallowing function (22)(23)(24). GPi DBS has also been used to treat various dystonia (25)(26)(27)(28), including Meige syndrome (29)(30)(31)(32), and its effect on the swallowing function is also of interest to review compared to that in PD.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 2,015 citations identified by the search, 1,945 were screened for eligibility after duplicates were removed. Of these, 144 studies were considered potentially eligible, requiring full-text review, and 26 were found to meet all criteria for inclusion and synthesis ( Alfonsi et al, 2017 ; Argolo et al, 2013 ; Athukorala et al, 2014 ; Baijens et al, 2013 ; Bushmann et al, 1989 ; Ciucci et al, 2008 ; El Sharkawi et al, 2002 ; Fuh et al, 1997 ; Hirano et al, 2015 ; Hunter et al, 1997 ; Khedr et al, 2019 ; Kondo et al, 2017 ; Kulneff et al, 2013 ; Lengerer et al, 2012 ; Michou et al, 2014 ; Miles et al, 2017 ; Monte et al, 2005 ; Pitts et al, 2009 ; Stegemöller et al, 2017 ; Sundstedt, Holmén, et al, 2017 ; Sundstedt et al, 2012 ; Tawadros et al, 2012 ; Tison et al, 1996 ; Troche et al, 2010 ; Warnecke et al, 2016 ; Xie et al, 2015 ). Interrater agreement between two reviewers was calculated, using the kappa statistic, to be .59 (moderate agreement) at the title and abstract screening stage and .71 (substantial agreement) at the full-text review stage ( McHugh, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 24 studies reporting descriptive statistics regarding the age of participants with PD, 21 reported a mean or median age of over 60 years for the patient participants ( Alfonsi et al, 2017 ; Athukorala et al, 2014 ; Bushmann et al, 1989 ; Ciucci et al, 2008 ; El Sharkawi et al, 2002 ; Fuh et al, 1997 ; Hirano et al, 2015 ; Hunter et al, 1997 ; Khedr et al, 2019 ; Kulneff et al, 2013 ; Michou et al, 2014 ; Miles et al, 2017 ; Monte et al, 2005 ; Pitts et al, 2009 ; Stegemöller et al, 2017 ; Sundstedt et al, 2012 ; Tawadros et al, 2012 ; Tison et al, 1996 ; Troche et al, 2010 ; Warnecke et al, 2016 ; Xie et al, 2015 ). The remaining three studies had participants with ages between 45 and 60 years ( Argolo et al, 2013 ; Lengerer et al, 2012 ; Sundstedt, Holmén, et al, 2017 ). Across the 21 studies reporting the gender distribution of included participants, the mean proportion of male participants was 70% ( Alfonsi et al, 2017 ; Argolo et al, 2013 ; Athukorala et al, 2014 ; Baijens et al, 2013 ; Bushmann et al, 1989 ; Ciucci et al, 2008 ; El Sharkawi et al, 2002 ; Hirano et al, 2015 ; Hunter et al, 1997 ; Kondo et al, 2017 ; Kulneff et al, 2013 ; Lengerer et al, 2012 ; Michou et al, 2014 ; Miles et al, 2017 ; Monte et al, 2005 ; Pitts et al, 2009 ; Stegemöller et al, 2017 ; Sundstedt, Holmén, et al, 2017 ; Sundstedt et al, 2012 ; Troche et al, 2010 ; Xie et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation